2014
DOI: 10.1103/physrevb.90.014414
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic theory for thermal-gradient-driven domain-wall motion

Abstract: Spin waves (or magnons) interact with magnetic domain walls (DWs) in a complicated way that a DW can propagate either along or against magnon flow. However, thermally activated magnons always drive a DW to the hotter region of a nanowire of magnetic insulators under a temperature gradient. We theoretically illustrate why it is surely so by showing that DW entropy is always larger than that of a domain as long as material parameters do not depend on spin textures. Equivalently, the total free energy of the wire… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 36 publications
1
38
0
Order By: Relevance
“…The DW is inside the TG (∇T (X DW ) = 0) and its motion can be attributed mostly to the ET. [19][20][21] In the Magnonic case the motion could be given by a magnons stream passing adiabatically through the DW, but also by the effect of an averaged ET. Note that thermal magnons, apart from the µST T , also introduce an averaged ET 21,23 : where the temperature is higher, the averaged M s (over more cells) is lower (as in the Entropic case) due to higher thermal fluctuation.…”
Section: Resultsmentioning
confidence: 99%
“…The DW is inside the TG (∇T (X DW ) = 0) and its motion can be attributed mostly to the ET. [19][20][21] In the Magnonic case the motion could be given by a magnons stream passing adiabatically through the DW, but also by the effect of an averaged ET. Note that thermal magnons, apart from the µST T , also introduce an averaged ET 21,23 : where the temperature is higher, the averaged M s (over more cells) is lower (as in the Entropic case) due to higher thermal fluctuation.…”
Section: Resultsmentioning
confidence: 99%
“…This would also allow one to investigate novel phenomena such as domain-wall motion in a magnetic insulator, which is in contrast to the well-established domain-wall motion in conductors, not driven by electronic spin currents [27] but by spin waves [28,29]. Recent results in the field of spin caloritronics have shown that the spin waves can also be thermally excited by the spin Seebeck effect [30] and are capable of moving magnetic domains [31][32][33][34][35]. However, a more detailed analysis of the thermally excited domain wall motion has not been possible, so far, as experimental observations are currently limited only to bulk materials due to the relatively weak signal in YIG.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 However, a domain wall in a temperature gradient can experience additional torques besides the purely magnonic ones, for instance the exchange stiffness can vary with temperature. 5,[16][17][18][19][20][21] Characteristically, these torques can induce a Walker breakdown, upon which the domain wall is deformed as it moves. 22 In ferromagnets, previous studies of domain wall dynamics due to magnonic torques have considered the response of a static wall to first-order spin-wave excitations.…”
Section: Introductionmentioning
confidence: 99%